Tell about Night Flowers : Eudora Welty's Gardening Letters, 1940-1949 - Welty, Eudora, 1909-2001 (Book collections on Project MUSE., 2013)
This book presents previously unpublished letters by Eudora Welty. Welty published many of her best-known works in the 1940s: A Curtain of Green, The Wide Net, The Robber Bridegroom, Delta Wedding, and The Golden Apples. During this period, she also wrote hundreds of letters to two friends who shared her love of gardening. One friend, Diarmuid Russell, was her literary agent in New York; the other, John Robinson, was a high school classmate and an aspiring writer who served in the Army in WWII, and long the focus of Welty's affection. Welty's lyrical, witty, and poignant discussions of gardening and nature are delightful in themselves; they are also figurative expressions of Welty's views of her writing and her friendships. Taken together with thirty-five illustrations, they form a poetic narrative of their own, chronicling artistic and psychic developments that were underway before Welty was fully conscious of them.